2011
DOI: 10.1021/om1011165
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement/Fragmentation Reactions of Oligosilanes with Aluminum Chloride

Abstract: Reinvestigation of the Lewis acid catalyzed rearrangement of some open-chain permethyloligosilanes with the Al(Fe)Cl3 catalyst system exhibited several cases of additional reactivity: namely, a fragmentation/cyclization reaction. Introduction of (trimethylsilyl)methyl substituents into the oligosilane substrates strongly facilitated this reaction, yielding cyclic or bicyclic carbacyclosilanes. Investigations concerning the composition of the catalyst system indicated that the incorporation of about 0.1% FeCl3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…In the course of our studies concerning the Lewis acid catalyzed rearrangement reactions of oligosilanes [30–32] we found that rearrangement of trimethylgermyl substituted oligosilanes led to the formation of silyl substituted germanes [33] . The deliberate introduction of germanium atoms was recognized as a unique way to generate germanium containing oligosilanes.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our studies concerning the Lewis acid catalyzed rearrangement reactions of oligosilanes [30–32] we found that rearrangement of trimethylgermyl substituted oligosilanes led to the formation of silyl substituted germanes [33] . The deliberate introduction of germanium atoms was recognized as a unique way to generate germanium containing oligosilanes.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the selective and exclusive formation of cation 8 with no indications for the presence of cation 14 contrasts the experimental finding for the actual rearrangement reaction ( Scheme 2 ), with both oligosilanes 3 and 4 formed initially in equal amounts. 31 In an attempt to tackle this aspect, we started a detailed computational investigation of the PES connecting the isomeric cations 7 , 8 , and 14 . The result of these calculations revealed a delicate balance between inter- and intramolecular stabilization of the silyl cation center.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 2 provides an example for this type of reaction in which the linear oligosilane 2 is transformed initially into its branched isomers 3 and 4 . 25 , 31 We have studied the reaction shown in Scheme 2 by ionizing close derivatives of oligosilane 2 at low temperature and characterized important cationic intermediates, which has allowed the formulation of a detailed mechanism for this reaction. In addition, the accompanying computational studies have provided clear indications that favorable attractive London dispersion forces 32 in these intermediates drive these types of skeletal rearrangement reactions in the direction of branched products such as 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Compound 18 with phenyl groups on the 1,2-disilanylene unit (Figure 4) was synthesized in a similar way by reaction of tris(trimethylsilyl)silyl potassium with the 1,2-ditriflate obtained from 1,2-dimethyltetraphenyldisilane. Also, compound 19 was prepared in a similar way (Scheme 5) and was then converted further to compound 20 by AlCl 3 catalyzed isomerization (Figure 4) [21].…”
Section: Resultsmentioning
confidence: 99%
“…All chemicals were obtained from different suppliers and were used without further purification. 1,2-Dichlorotetramethyldisilane [48,49], 1,3-dichlorohexamethyltrisilane [48,49], 1,4-dichlorooctamethyltetrasilane [48,49], tetrakis(trimethylsilyl)silane [50], isopropylbis(trimethylsilyl)silylpotassium [19], 2,5-bis(trimethylsilyl)dodecamethylhexasilane ( 3 ) [51], bis(trimethylsilyl)triisopropylsilylsilylpotassium [19], tris(trimethylsilyl)triisopropylsilylsilane [19], 2,2,5-tris(trimethylsilyl)undecamethylhexasilane [21], 2,2,6,6-tetrakis(trimethylsilyl)dodecamethylheptasilane ( 25 ) [52], 2,2,5-tris(trimethylsilyl)undecamethylhexasilane [21], tris(trimethylsilyl)]trimethoxysilylsilane [53], 1,2-dimethyltetraphenyldisilane [54] and 1,1,4,4,-tetrakis(trimethylsilyl)octamethylcyclohexasilane ( 26 ) [33] were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%